PENGGUNAAN KECERDASAN BUATAN (AI) DALAM KEUSAHAWANAN ISLAM: PELUANG DAN CABARAN DI NEGERI KEDAH: The Use of Artificial Intelligence (AI) in Islamic Entrepreneurship: Opportunities and Challenges in the State of Kedah - Abd Muin , Mohd Adib; Shuib, Mohd Sollehudin; Che Omar, Azizah; Man @ Othman, Wazin; Ismail, Izatul Akmar; Abdullah, Shuhairimi (Online Journal of Islamic Management and Finance (OJIMF), 2025)
This study examines the use of artificial intelligence (AI) in Islamic entrepreneurship in the State of Kedah, with the aim of identifying the opportunities and challenges faced by Muslim entrepreneurs in utilizing technology. In the era of Industrial Revolution 4.0, AI is gaining more and more attention as a tool that can speed up the process innovation, improve operational effectiveness, and help make smarter business decisions. However, the use of AI in the context of Islamic business is still at an early stage, especially among micro and small entrepreneurs who face constraints in terms of technical skills, investment costs, and sharia compliance requirements. Through a qualitative approach involving secondary data analysis and interviews with entrepreneurs and technology experts, this study found that AI has the potential to optimize customer service, expand market reach, and increase efficiency in the management of Islamic entrepreneurial operations. However, there are major challenges such as lack of awareness, high implementation costs, and the need for sharia compliance monitoring in each phase of technology use. This study suggests that there be support in the form of AI training specifically for Muslim entrepreneurs as well as creating a syariah compliance guide in the use of technology to ensure that AI is used ethically and based on Islamic principles. The implications of this study show the great potential of AI in strengthening the competitiveness of Muslim entrepreneurs in the state of Kedah while strengthening Islamic values ​​in high-tech business.